2009
DOI: 10.1177/0886260509334412
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Immobility in Childhood Sexual Abuse Survivors and Its Relationship to Posttraumatic Stress Symptomatology

Abstract: Past research has shown that 37% to 52% of sexual assault survivors report experiencing a set of peritraumatic responses, which include gross motor inhibition, analgesia, and fixed or unfocused staring. This response set closely resembles a set of unconditioned responses, collectively known as Tonic Immobility (TI). This study examined TI among childhood sexual abuse (CSA) survivors and its relation to PTSD symptomatology. Participants were 131 female college undergraduates who completed questionnaires assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 30 publications
4
38
0
2
Order By: Relevance
“…31, nº 3 (octubre) with the findings of Bados et al (2008). Likewise, given the known association between TI and post-traumatic symptoms (Bovin et al, 2008;Humphreys et al, 2010;RochaRego et al, 2009) the importance of this type of event is congruent with the observation of current post-traumatic symptoms being greater when the earlier trauma involved physical violence in the family, sexual violence or childhood sexual abuse (Frazier et al, 2009;Owens & Chard, 2006;Vrana & Lauterbach, 1994).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…31, nº 3 (octubre) with the findings of Bados et al (2008). Likewise, given the known association between TI and post-traumatic symptoms (Bovin et al, 2008;Humphreys et al, 2010;RochaRego et al, 2009) the importance of this type of event is congruent with the observation of current post-traumatic symptoms being greater when the earlier trauma involved physical violence in the family, sexual violence or childhood sexual abuse (Frazier et al, 2009;Owens & Chard, 2006;Vrana & Lauterbach, 1994).…”
Section: Discussionsupporting
confidence: 65%
“…In these cases, TI reduces the likelihood that the predator will continue to attack and thus increases the chances of escape and survival (Bracha, 2004;Moskowitz, 2004). TI has not been widely studied in humans, and although some authors argue that it may have an adaptive value in certain situations of physical or sexual aggression where fighting or escape is not possible (see Heidt et al, 2005), it has been found to be moderately correlated with post-traumatic symptoms (Abrams, Carleton, Taylor, & Asmundson, 2009;Abrams, Carleton, & Asmundson, 2012;Bovin, Jager-Hyman, Gold, Marx, & Sloan, 2008, Humphreys, Sauder, Martin, & Marx, 2010Heidt et al, 2005;Rocha-Rego et al, 2009) and to be a predictor for the emergence of intrusive memories (Hagenaars & Putman, 2011), the development of post-traumatic symptoms (Bovin et al, 2008;Humphreys et al, 2010;Rocha-Rego et al, 2009) and a poorer response to pharmacological treatment for post-traumatic stress disorder (PTSD) (Fiszman et al, 2008;Lima et al, 2010). Scaer (2014) has put forward one explanation for the association between a TI response, of which dissociation is a central element, and PTSD.…”
Section: *) Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both theories are concerned with the individual, both have demonstrated roles in the development and maintenance of PTSD and SUD (Walsh, DiLillo, & Messman-Moore, 2012;Humphreys, Sauder, Martin, & Marx, 2010). Emotion regulation refers to the set of processes by which an individual controls or moderates their emotions to more appropriately suit the situation.…”
Section: Overview Of This Researchmentioning
confidence: 99%
“…For example, fight-flight-freeze sensitivity (FFFS), a facet of rRST, can predict the development of PTSD, and the severity of the symptomatology (Humphreys, Sauder, Martin, & Marx, 2010).…”
Section: Overview Of This Researchmentioning
confidence: 99%